The Haughtiness and the Humility in Al Koran (Journal of the College of Education for Women, 2019)
Abstract What the research come to: 1- The presentation of the image of the proud person in this mortal life appeared in several styles such as (conversation) arousing the insert once and convincing in other time, (confirmation) in all its types، (argument) scolding with the gradual progress of time of the discourse .Interview and parallelism are two of these styles with the presences of the repetition style especially in the topics that has a reference to the theme of (pride) being implied not directly stated. The Koran discourse varied in its reference to the theme of pride according to the context which is mentioned directly (eighteen times) which formed one third of the number of times of its mentioning in the Holy Koran and in different forms. 2- The verb with additional letters is repeated (‫ﺘﻜﺒﺮ‬Ǵ‫ ﯾﺴ‬-‫ﺘﻜﺒﺮ‬Ǵ‫ )اﺳ‬and the present participle that is derived from the verb more than others giving the sense of the request and “he becoming” and the sense of how great the guilt which the request left in the person's self. 3- The verbs mentioned more than the nouns referring that this urgent adjective is not natural creatures and changeable not adherent, yet what is constant is modesty, and because the verb is variable and changeable the call was repeated to dismiss to renounce pride and be back to the origins. Pride is also mentioned in the form of present participlereferring to the event either described with atheism or arrogant orin the sense of him being chained with his insistence that isbecause the present principle is not in the reality of perception butnot in the order of Allah (be raised far above) in the changing andvariable form for the future. The moral evidence to understand the meaning of the eventcomes from the side of the meaning attributed to the additionalletters of the forms and what the form (‫ﺘﻔﻌﻞ‬Ǵ‫ )اﺳ‬serve as request,power, and fault, also what the form (‫ﻞ‬Ǵ‫)ﺗﻔﻌ‬include of artificiality andexposition to the reverence which appears in the Koran discoursein the form of adverb, describing the manner and restricting theverb, with the variety of types and subjects, leading to theassertion in its repletion overlapping and the sequence of itssentences. This proves the faith in “right” and calmness of the“self” in the believers, opposite it with the sense in the unbelieverslike lowness and disgrace. The image of reverence comes perfectly to include thecalmness of the heart and self organs and the entire creatureswhich is the reverence caused by faith in any doctrine and in anysituation with desire and fear in this mortal and in the ever afterthat is because the mortal evidence or one which shape the form.